Clinical guidelines: an evidence-based debate - Fereshte Farhadi; Masoumeh Abbasi-Asl; Negar Taleschian-Tabrizi; Mohammad Ali Hajebrahimi; Hadi Mostafaie; Sakineh Hajebrahimi (Tabriz University of Medical Sciences, 2019)
Background: This study aimed to evaluate the effectiveness of debate as a learning tool for changing audiences' views regarding the use of clinical guidelines in routine clinical practice. Methods: A debate scenario including different rationales for and against using guidelines in clinical practice, presented by the student section of Iranian Evidence Based Medicine Center of Excellence, was held at the first International Student Congress of Research Integrity and Evidence-Based Practice (Kish Island, Iran, December, 2015). The audience was first asked to check the papers given to them, and if they agreed to the terms, they were asked to choose,"Yes", "No", or "I don't know". Results: Of the 400 individuals participating in the congress, 100 were present during the scheduled debate time. Among the 71 people completing pretest questionnaires, 73% (52)answered "yes" to the question, "Should we use guidelines? "About 7% (5) claimed that we shouldn't use guidelines, and 20% (14) had no opinion about using them. Following the debate,the participants who chose "yes" to the guidelines remained in favor of their use in clinical practice. Of the 14 who did not have an opinion for guideline use, all agreed to use guidelines in clinical practice. Surprisingly, the five participants who were against guideline implementation remained fixed in their view, continuing to disagree regarding their use in clinical encounters. Conclusion: Although we were unable to change the attitudes of physicians who were against the use of guidelines in clinical practice, the debate caused a positive shift among participants who did not have an opinion regarding their use in clinical scenarios.